1997
DOI: 10.7326/0003-4819-126-1-199701010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Myelinolysis after Correction of Hyponatremia

Abstract: Myelinolysis is a neurologic disorder that can occur after rapid correction of hyponatremia. Initially named "central pontine myelinolysis," this disease is now known to also affect extrapontine brain areas. Manifestations of myelinolysis usually evolve several days after correction of hyponatremia. Typical features are disorders of upper motor neurons, spastic quadriparesis and pseudobulbar palsy, and mental disorders ranging from mild confusion to coma. Death may occur. The motor and localizing signs of myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
196
3
29

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(229 citation statements)
references
References 0 publications
1
196
3
29
Order By: Relevance
“…Some authorities have suggested that hypertonic saline should be used only in critical care units (12) or that it be limited to patients with repeated convulsions, agitated confusion, or coma (13). At our institution, hypertonic saline is permitted outside the critical care units, but oversight by nephrologists is strongly encouraged and is required for administration of Ͼ200 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Some authorities have suggested that hypertonic saline should be used only in critical care units (12) or that it be limited to patients with repeated convulsions, agitated confusion, or coma (13). At our institution, hypertonic saline is permitted outside the critical care units, but oversight by nephrologists is strongly encouraged and is required for administration of Ͼ200 ml.…”
Section: Discussionmentioning
confidence: 99%
“…The correction of hyponatremia should be slow enough (less than 10 mmol/L in a 24-hour period) to avoid any risk for central pontine myelinolysis, which occurs more often in chronic than in acute hyponatremia. 21 Studies of combination therapy are necessary to establish whether VPA could prevent the diuretic-induced hyponatremia occurring in approximately 25% of patients and increase the efficacy of treatment. Studies in rats simultaneously treated with high doses of furosemide did not show any decrease in aquaretic effect of VPA, nor interaction of VPA with the natriuretic effect of furosemide, which suggests that combination of these treatments could be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of symptoms depends on the degree and rate of development of hyponatremia. A rapid decrease in sodium levels may lead to coma and seizures, but if hyponatremia develops slowly, patients are much less symptomatic 4 . The risk factors for development of ODS after correction of chronic hyponatremia include hypokalemia, malnutrition, chronic alcoholism 5 , hypoxia 6 , burn injury, surgical removal of pituitary tumor and those who have undergone orthotopic liver transplant 7 .…”
Section: Discussionmentioning
confidence: 99%